The Effect Of Nostalgic Instrumental Music Therapy On Reducing Stress Levels In The Elderly With Working Families in The Pandanwangi Public Health Center, Malang City: The Effect Of Nostalgic Instrumental Music Therapy On Reducing Stress Levels In The Elderly With Working Families in The Pandanwangi Public Health Center, Malang City - Ananda Candra Waskita Wijaya; Imam Subekti; Edy Suyanto (Poltekkes Kemenkes Malang, 2023)
Stress in the elderly can occur due to several factors. Both internal and external factors. Stress management can be done non-pharmacologically, one of which is music therapy. The aim of this research is to determine the effect of nostalgic instrumental music therapy on changes in stress levels in elderly people with families who work in the Pandanwangi Health Center working area, Malang City. This research used a pre-experimental design, namely carrying out interventions and measurements carried out more than once, where the researcher carried out the intervention, namely nostalgic instrumental music, 2 times with a One Group Pretest Posttest design. The total sample was 30 respondents. Stress measurements were carried out before and after giving music therapy 2 times for 1 week. The analysis in this study used a paired t-test comparison test with Alpha results </= 0.05. The research results showed that almost all 83.2% experienced a decrease in stress levels and the rest had constant stress levels. The statistical test results show that the P value sig-2 tailed is 0.000, which means there is a significant influence between the provision of music therapy on changes in stress levels. It is hoped that elderly people who have been left behind to work by their families can apply nostalgic instrumental music therapy to reduce stress levels when alone at home